Household Livelihood Security Index (HLSI) of livestock farmers vis-à-vis other occupational groups in rural Tamil Nadu - G. Senthil Kumar; K.N. Selvakumar; M. Prabu; A. Serma Saravana Pandian; C. Valli; P. Thilakar (Indian Journal of Veterinary and Animal Sciences Research, 2025)
An attempt was made to compare the Household Livelihood Security Index (HLSI) of Livestock farmers vis-à-vis other occupational groups in rural Tamil Nadu using randomly selected 540 sample households from six poverty prone sample districts. HLSI was constructed for each sample household based on the previous literature and variations among different occupational groups and districts were compared. The HLSI was found to be the highest among crop + livestock farmers (0.4887), followed by fishermen (0.4821), non-farm (0.4701), livestock farmer (0.4583), crop cultivators (0.4347) and agricultural labourers (0.3860) with the overall HLSI of 0.4435. Among different districts, HLSI was found to be the lowest in Pudukottai district (0.3815), followed by Ariyalur (0.4324) andRamanathapuram (0.4455). Overall, it could be concluded that health and infrastructure indices among different occupations and locality was calculated to be higher when compared to other domains. The study revealed that there is an urgent need to improve the empowerment index irrespective of the locality and occupations.